AN IMPLEMENTION OF INTEGRATIVE ACTIVE LEARNING STRATEGIES IN ISLAMIC RELIGIOUS EDUCATION - Ikhrom, Ikhrom (Jurnal Al-Fatih, 2023)
This article aims to reveal the implication of active-integrative learning strategies in Islamic religious education (PAI) subjects. This phenomenological qualitative research relies on observational data, interviews, and documentation. The results indicate that there are some problems in implementing active-integrative learning strategies in PAI subjects. This problem stems from the teacher's lack of steady perspective on the reality and ideality of the material and learning objectives of PAI. This perspective problem has an impact on teachers' courage in implementing active-integrative learning strategies in PAI learning in the classroom. The study recommends that teachers need to renew their perspective on the meaning of integrating material and learning objectives of Islamic religious education, as well as the ability and courage to apply active and integrative learning in learning Islamic religious education.